PENERAPAN MODEL PEMBELAJARAN NUMBERD HEAD TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR SISWA MATA PELAJARAN EKONOMI KELAS XI SMA NEGERI 6 HALMAHERA TIMUR - Yuliantri Lahura Gusa; Datje Renjaan; Narilah A Tuara (Program Studi Pendidikan Ekonomi Institut Sain dan Kependidikan (ISDIK) Kie Raha Maluku Utara, 2023)
The purpose of this study was to determine the improvement in learning outcomes of class XI students of SMA Negeri 6 East Halmahera in the subject of economic education using the NHT type cooperative model. The research design used was classroom action research carried out in two cycles. Each cycle consisted of planning, implementation, observation, and reflection stages. The subjects in this study were class XI students. Academic year 2022/2023 totaling 24 students consisting of 12 male students and 12 female students, as well as the economic education subject teacher. Based on the analysis of research data, the results of observations on the percentage of student learning activities during learning experienced an increase from cycle I of 65 to 85 in cycle II. Likewise, teacher performance in cycle I reached 75 and increased to 88.3 in cycle II. Meanwhile, the percentage of student learning outcomes completion in cycle I reached 50% with a class average value of 80 and in cycle II student learning completion increased to 91.6% with a class average value of 90. Based on the results of the study above, it can be concluded that through the application of the NHT type cooperative model has succeeded in increasing the Activities and Learning Outcomes of the economic education subject of APBD and APBN material for class XI students of SMA Negeri 6 Halmahera Timur